2017
DOI: 10.1186/s12885-017-3559-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal influence of endocrine therapy with tamoxifen and chemotherapy on nutritional risk and obesity in breast cancer patients

Abstract: BackgroundThe effect of endocrine therapy with tamoxifen (TMX) on weight gain has been reported in the literature, but the outcomes are still controversial. Moreover, previous treatment options, such as chemotherapy (CT), also include body changes. The focus of this study was to verify the temporal influence of endocrine therapy with TMX on nutritional risk and obesity and its association with CT in breast cancer patients.MethodsIn this cross-sectional study, 84 breast cancer surviving women were evaluated dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…This fact can be related to age and nutritional status at diagnosis, therapy used during the treatment, tumour characteristics, menopausal status [ 10 ], reduced basal metabolic rate and total energy expenditure, decreased physical activity, sleep disorders, abnormal thyroid function [ 11 ] and frequent use of steroids during CT [ 12 ]. In addition, our group recently found that women with BC on endocrine therapy with Tamoxifen are mostly overweighed and obese, most evidently in women who received CT, and who were at the beginning of the treatment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fact can be related to age and nutritional status at diagnosis, therapy used during the treatment, tumour characteristics, menopausal status [ 10 ], reduced basal metabolic rate and total energy expenditure, decreased physical activity, sleep disorders, abnormal thyroid function [ 11 ] and frequent use of steroids during CT [ 12 ]. In addition, our group recently found that women with BC on endocrine therapy with Tamoxifen are mostly overweighed and obese, most evidently in women who received CT, and who were at the beginning of the treatment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…42 In addition, higher BMI, WC, and BF values in the first years of endocrine therapy for BC can be influenced by previous treatments such as chemotherapy. 43 Therefore, the greater functional disability in the first years could have arisen from the prolonged effects of previous treatments before endocrine therapy, such as chemotherapy or the concomitant steroids provided to patients with this treatment, rather than AI use. Similarly, in a recent study published by our group, we found a significant effect of the interaction of chemotherapy with a shorter duration of tamoxifen use relative to adiposity parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a recent study published by our group, we found a significant effect of the interaction of chemotherapy with a shorter duration of tamoxifen use relative to adiposity parameters. 43 In addition, psychological factors such as anxiety and depression are common in the first years of endocrine therapy 44 and may interfere with changes in body composition. To our knowledge, ours is the first study to compare groups at different duration of AI therapy with body composition and FC.…”
Section: Discussionmentioning
confidence: 99%
“…Women in the highest quintile of BMI are twice as likely to die from breast cancer compared to women without obesity [ 6 ]. Endocrine therapy with tamoxifen is associated with weight gain/obesity, with a higher risk for women who first undergo chemotherapy [ 7 ]. During menopause, estradiol levels decrease and often contribute to weight gain/obesity as well [ 8 ].…”
Section: Introductionmentioning
confidence: 99%